Impact of Empowering Leadership on Employee Creativity by Motivation to Learn and Trust in Leader as a Mediation - Fitriani, Yayuk; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2018)
The purpose of this study is to determine the effect of empowering leadership on the employee creativity by motivation to learn and trust in leader as a mediation variable. The population in this study is all State-Owned Bank Employees in Semarang City. Methods of data collection using observation, interviews, and questionnaires. Sampling technique using multi-stage sampling technique. The sample size is 220 people. Methods of data analysis using descriptive analysis, goodness-fit model analysis, regression analysis, and path analysis. Data analysis using Structural Equation Model (SEM) with WarpPLS version 6.0. The results show that empowering leadership positively influences motivation to learn, trust in leader, and employee creativity. In addition, the results of the study also showed that motivation to learn and trust in leader have a positive effect on employee creativity. Furthermore, the motivation to learn and trust in the leader is able to mediate between empowering leadership on employee creativity. The conclusion of this research is to produce a creative employee, it takes the role of a leader who can empower his subordinates. The ability of leaders to empower their subordinates will have a good impact on their employees, especially increasing the motivation to learn and trust in leaders. So that employees are optimal in expressing their creativity in the workplace. Suggestions for state-owned banking management that is more able to pay attention to the needs of employees and give confidence in subordinates to participate in solving problems.